Transformasi Estetik Keramik Kasongan, Bantul, Yogyakarta - Muhamad Romadoni; Iwan Pranoto (Journal Pendidikan Ilmu Pengetahuan Sosial, 2023)
Kasongan ceramics experience aesthetic transformation over time. Changes in the art of Kasongan ceramics were initially limited to household items with designs limited to circles, rounds, and cylinders, changing into animal shapes with pasting decoration techniques, jars with paint finishing techniques or glass mosaics, and Loroblonyo sculptures with glaze finishing techniques. The manufacturing technique, which was initially limited to traditional techniques, has evolved over time in terms of tool preparation, embodiment, and finishing. This is evident in the work produced, which range from traditional techniques to temple techniques and finishing techniques using paint, glass, and glaze. The ceramic design that was originally intended to fulfill daily needs has undergone a design shift, namely toward a ceramic design that is not only functional (traditional), but also more oriented toward art product design (decoration) or practical art (functional decoration). External and internal factors that exist in the wider community influence the variety of products produced by ceramic artisans in Kasongan.